A king and a fool? : the succession narrative as a satire - Miller, Virginia (Research Fellow), (Biblical Interpretation Series;, 2019)
In A King and a Fool? The Succession Narrative as a Satire Virginia Miller applies a new version of Douglas Muecke's taxonomy of irony to the Succession Narrative. She argues that the narrative in 2 Samuel and 1 Kings has the essential feature of satire, namely, a pervasive sense of pejoratively critical irony. By her account, King David is the object of ironic attack, and therefore, an object of condemnation. Given that the primary purpose of satire is reform, Miller claims that the purpose of the Succession Narrative is a call for reform in the leadership of Israel.